Effects of pharmacological agents for neurogenic oropharyngeal dysphagia: A systematic review and meta‐analysis. Issue 3 (1st August 2021) - Cheng, Ivy; Sasegbon, Ayodele; Hamdy, Shaheen
Abstract: Background: This systematic review and meta‐analysis aimed to evaluate the effects of pharmacological agents for neurogenic oropharyngeal dysphagia based on evidence from randomized controlled trials (RCTs). Methods: Electronic databases were systematically searched between January 1970 and March 2021. Two reviewers independently extracted and synthesized the data. The outcome measure was changed in (any) relevant clinical swallowing‐related characteristics. Key results: Data from 2186 dysphagic patients were collected from 14 RCT studies across a range of pharmacotherapies. The pooled effect size of transient receptor potential (TRP) channel agonists was large compared to placebo interventions (SMD[95%CI] =1.27[0.74, 1.80], p < 0.001; I 2 = 79%). Data were limited for other pharmacological agents and the overall pooled effect size of these agents was non‐significant (SMD [95% CI] =0.25 [−0.24, 0.73]; p = 0.31; I 2 = 85%). When analyzed separately, large effect sizes were observed with Nifedipine (SMD[95%CI] =1.13[0.09, 2.18]; p = 0.03) and Metoclopramide (SMD[95%CI] =1.68[1.08, 2.27]; p < 0.001). By contrast, the effects of angiotensin‐converting enzyme (ACE) inhibitors (SMD[95%CI] = −0.67[−2.32, 0.99]; p = 0.43; I 2 = 61%), Physostigmine (SMD[95%CI] = −0.05[−1.03, 0.93]; p = 0.92) and Glyceryl Trinitrate (GTN) (SMD [95% CI] = −0.01 [−0.11, 0.08]; p = 0.78) were non‐significant. Within stroke patients, subgroup analysis showed that TRP channel agonists had a moderate pooled effect size (SMD[95%CI] =0.74[0.10, 1.39]; p = 0.02; I 2 = 82%) whereas the effects of other agents were non‐significant (SMD[95%CI] =0.40[−0.04, 0.84]; p = 0.07; I 2 = 87%). Conclusions & Inferences: Our results showed that TRP channel agonists, Nifedipine and Metoclopromide may be beneficial for neurogenic dysphagic patients. Large scale, multicenter clinical trials are warranted to fully explore their therapeutic effects on swallowing. Abstract : Our systematic review and meta‐analysis found that transient receptor potential (TRP) channel agonists, Nifedipine and Metoclopromide may be beneficial for neurogenic dysphagic patients. Large scale, multicenter clinical trials are warranted to fully explore their therapeutic effects on swallowing.